[Sikhay sa kabila ng paalam [videorecording] - Cultural Center of the Philippines; Philippines. National Commission for Culture and the Arts. (Manila NCCA)
A performance based on Dr. Jose Rizal's "Mi Ultimo Adios."
VHS.
Keywords: Theater -- Philippines